Does top managers’ skills moderate the debt-stock returns relationship in Malaysia? - Matemilola, Bolaji Tunde; Amin Noordin, Bany Ariffin; Wan Ngah, Wan Azman Saini (Universiti Malaysia Sarawak, 2019)
Traditional theorists recognize that stockholders benefit from top managers’ decisions; but, top managers’ skills are not explicitly analysed in their theoretical model. This article examines the moderating effects of top managers’ skills on the debt-stock return relationship. The two-step system generalized method of moments results show top managers skills positively moderate the book debt and stock return relationship. Moreover, top managers’ skills have direct positive effect on stock returns. The results are robust using an alternative measure of debt, as top managers’ skills positively moderate the market debt and stock returns relationship. The findings suggest that top managers’ possessing strong skills maximize tax-shield benefits of debt and they increase stockholders’ returns.